2022
DOI: 10.3389/fmicb.2022.859732
|View full text |Cite
|
Sign up to set email alerts
|

Genital Mycoplasmas and Biomarkers of Inflammation and Their Association With Spontaneous Preterm Birth and Preterm Prelabor Rupture of Membranes: A Systematic Review and Meta-Analysis

Abstract: Genital mycoplasmas (GM), such as Mycoplasma hominis, Mycoplasma genitalium, Ureaplasma parvum, and Ureaplasma urealyticum are commonly associated with spontaneous preterm labor (SPTL), spontaneous preterm birth (PTB), and preterm prelabor rupture of membranes (PPROM). This study determined the association between GM and such adverse pregnancy outcomes. We searched for studies published 1980–2019 in MEDLINE, EMBASE, and Web of Science. Studies were eligible when GM was detected during pregnancy. We included 93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 97 publications
6
27
0
Order By: Relevance
“…This supports the increased production of IL-6, IL-8, and GM-CSF in the infected VECs we observed, which are pro-in ammatory mediators that can be transported by EVs [36]. This in vitro model somewhat substantiates the ndings of our recent systematic review on genital Mycoplasma [37] where we showed that U. parvum is not a great pathogen in the cervicovaginal environment unlike other virulent species (e.g., Gardnerella). Another recent study concluded that cervicovaginal Mycoplasma infection (including Mycoplasma hominis and Ureaplasma spp.)…”
Section: Discussionsupporting
confidence: 90%
“…This supports the increased production of IL-6, IL-8, and GM-CSF in the infected VECs we observed, which are pro-in ammatory mediators that can be transported by EVs [36]. This in vitro model somewhat substantiates the ndings of our recent systematic review on genital Mycoplasma [37] where we showed that U. parvum is not a great pathogen in the cervicovaginal environment unlike other virulent species (e.g., Gardnerella). Another recent study concluded that cervicovaginal Mycoplasma infection (including Mycoplasma hominis and Ureaplasma spp.)…”
Section: Discussionsupporting
confidence: 90%
“…Ureaplasma parvum and U. urealyticum were also present in the amniotic fluid of patients with preterm premature rupture of membranes (pPROM) and PTB. [26][27][28][29] The mechanism by which Ureaplasma spp. colonize, compromise the barriers of the cervix, and ascend into the amniotic cavity is not yet fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these bacteria can breach the cervical barrier and invade the fetus within the uterine cavity. Ureaplasma parvum and U. urealyticum were also present in the amniotic fluid of patients with preterm premature rupture of membranes (pPROM) and PTB 26–29 . The mechanism by which Ureaplasma spp.…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria associated with sPTB differ between studies and appear to vary significantly at the individual level, dependent on many factors, including specific combinations of bacteria, strains of bacteria, bacterial load, sites of bacterial localization, kinetics and timing of infection, the level of inflammation induced, as well as ethnicity and geographical region. 40,48 These differences hinder the development of accurate, universal diagnostics and effective strategies to treat women at risk of sPTB.…”
Section: Chlamydia Trachomatis Neisseria Gonorrhoeae Treponema Pallid...mentioning
confidence: 99%